Real-world outcomes in thoracic cancer patients with severe Acute respiratory syndrome Coronavirus 2 (COVID-19): Single UK institution experience. (2020) - Cui, Wanyuan; Yousaf, Nadia; Bhosle, Jaishree; Minchom, Anna; Nicholson, Andrew G.; Ahmed, Merina; McDonald, Fiona; Locke, Imogen; Lee, Richard; O'Brien, Mary; Popat, Sanjay
Highlights: The immediate morbidity from COVID-19 is high in UK thoracic cancer patients. Mortality, hospitalisation and treatment interruption rates were high. All patients who died were current or ex-smokers. Abstract: Background: UK COVID-19 mortality rates are amongst the highest globally. Controversy exists on the vulnerability of thoracic cancer patients. We describe the characteristics and sequelae of patients with thoracic cancer treated at a UK cancer centre infected with COVID-19. Methods: Patients undergoing care for thoracic cancer diagnosed with COVID-19 (RT-PCR/radiology/clinically) between March-June 2020 were included. Data were extracted from patient records. Results: Thirty-two patients were included: 14 (43%) diagnosed by RT-PCR, 18 (57%) by radiology and/or convincing symptoms. 88% had advanced thoracic malignancies. Eleven of 14 (79%) patients diagnosed by RT-PCR and 12 of 18 (56%) patients diagnosed by radiology/clinically were hospitalised, of which four (29%) and 2 (11%) patients required high-dependency/intensive care respectively. Three (21%) patients diagnosed by RT-PCR and 2 (11%) patients diagnosed by radiology/clinically required non-invasive ventilation; none were intubated. Complications included pneumonia and sepsis (43% and 14% respectively in patients diagnosed by RT-PCR; 17% and 11% respectively in patients diagnosed by radiology/clinically). In patients receiving active cancer treatment, therapy was delayed/ceased in 10/12 (83%) and 7/11 (64%) patients diagnosed by RT-PCR and radiology/clinically respectively. Nine (28%) patients died; all were smokers. Median time from symptom onset to death was 7 days (range 3–37). Conclusions: The immediate morbidity from COVID-19 is high in thoracic cancer patients. Hospitalisation and treatment interruption rates were high. Improved risk-stratification models for UK cancer patients are urgently needed to guide safe cancer-care delivery without compromising efficacy.